Religious stories for children in Iraq From (1922 to 1968) (Journal of the College of Basic Education, 2022)
In the name of God and peace and blessings be upon the Messenger of God and the good, pure family and from his family, but after: The Almighty said in the text of his dear book:﴿ We are the most good to you, the best of the story is what we have revealed to you, and this is the Qur’an. mouthpiece This is what prompted the story writers, when they were writing their stories for children in particular, to turn to this resource and draw from it what enriches their stories and enriches the souls of the readers of their stories among the children, so that it becomes the best tools for carving in their minds goodness and good morals.